NON INVASIVE PAIN MANAGEMENT IN POST PARTUM MOTHER WITHEVIDENCE BASED PRACTICE APPROACH - Nikmatur Rohmah (Universitas Airlangga, 2017)
Introduction: Pain is a sensation of discomfort that most post-partum mothers complain about, in the case of prolonged pain, the risk of post-partum blues is higher. The usage of evidence based practice method gives a bigger opportunity for nurse and medical attendants to think more critically in making decisions and in performing the appropriate treatment in accordance with the patient's problem and uniqueness. This research aimed to applicate management of non-invasive pain on post partum mother through the approach of evidence based practice. Method: This was a case-study, performed to client Mrs. A P1-1 A0 post sectio caesarea day 1 as there is an indication of suspect cepalo pelvis disproportion secondary arrest. Data were collected at maternity room, dr. Soebandi Regional General Hospital. Using interview, observation, and physical examination. Data analysis was conducted through a descriptive analysis. Result: Through a careful nursing, it is found out that pain location and spreading that generally spotted at the patient's back during the contraction in the uterus, occurred around the shoulders when evidence-base practice is applied. The basic principle of applying an intervention to non invasive pain based on evidence-base practice are: cutaneous stimulation and distraction, while massaging area was set on the face, while the distraction media was interaction with the baby. Evaluation on evidence -based practice showed that pain is reduced to scale 2, while face and mobilitation become more relaxed. Discussion: Massage was intended to stimulated the production of endorphine and dinorphine that play an important roke to block the pain transmission through the descendent control system. Interaction with the baby was intended to function as a distraction media to dominate the incoming impuls into the ascendant control system,which further may close the gate of the pain transmitter. Both of the interventions were axpected to work synergically in reducing pain, since post-partum pain can be relieved more quickly when more than one technique are applied. Thus, to reduce post-partum pain, facial massage and interaction with the baby as non-invasive treatments are of important, respectively.